Study of Coronary Atherosclerosis Using Blood Residence Time - Hashemi, Javad; Patel, Bhavesh; Chatzizisis, Yiannis S.; Kassab, Ghassan S. (Frontiers in Physiology, 2021)
Computational fluid dynamic-based modeling is commonly used in stenosed and stented coronary artery to characterize blood flow and identify hemodynamics factors that could lead to coronary stenosis. One such factor is the residence time (RT), which is important for investigating stenosis and restenosis progression. The current method to calculate RT, known as the relative residence time (RRT) method, does not provide the original scale of RT and only provides a relative value. We recently introduced a novel method, designated as RT method, based on developing the advection-diffusion equation with a scalar to calculate the absolute residence time. The goal of this study was to compare both methods. Our results show that both could detect regions with a high risk of stenosis and restenosis, but the RT method is also able to show the recirculation zone using pathlines in the lumen and quantify actual RT. Moreover, RT method also provided blood flow pathlines, and is correlated to wall shear stress (WSS), oscillatory shear index (OSI), RRT, and Localized Normalized Helicity (LNH) which are other critical factors to gauge stenosis severity and assess stenting in bifurcations coronary.